Tinjauan Sosiologi Pendidikan: Terhadap Kekerasan Dalam Dunia Pendidikan - Nurhidayah Nurhidayah (Journal on Education, 2023)
One of the interesting incidents that is currently receiving attention in the world of education is related to violence (bullying) at school. Bullying at school is a problem that often occurs and has a negative impact on the social order at school. The purpose of this research is to describe bullying in schools from an educational sociology perspective. The method used in this research is case studies and literature reviews. The results obtained from this research are the main causes of bullying in schools due to the decline in the behavior of students who currently lack manners, morals and manners for both teachers and students. In the context of educational sociology, bullying is considered a social phenomenon that occurs in the school environment. Sociology of education also enhances the importance of the role of schools, families and communities in preventing bullying. Both families, schools and the community can provide education and training about the importance of noble morals, good manners, tolerance, respect for elders and others. Some social controls and efforts to overcome bullying behavior that can be provided by schools include consulting counseling services and carrying out strict supervision, providing warnings and threats, and can also provide sanctions.